Production of Pure Rice Bran Wax - Saisanom Praditdoung; Nuatong Vananuvat; Manee Saeng ngern (Agriculture and Natural Resources, 1990)
Rice bran wax is a source of natural waxes and is considered as a waste from rice bran oil industries. Recovering of rice bran waxes by fractionally crystallization with solvents will be useful in making wax emulsion, this will add up value to rice industries. Preparation of the pure rice bran wax was carried out by using two different solvent methods. Yields as well as physical and chemical properties of the waxes were determined. The results showed that the use of benzene as the solvent gave 7-8% wax compared to 17-18% yield when purifying first with hexane and subsequently crystallized with isopropanol at 5oC. Both samples of waxes produced were quite hard and dry but the color varied from brown to tan. Their physical and chemical properties were similar and met the wax specification of the U.S.F.D.A. approval for food uses. Their properties were also very much similar to those of carnauba wax which is widely used in the industries.